Revision of China’s marine environmental protection law: history, background and improvement - Liu, Ruiqiang (Frontiers in Marine Science, 2024)
The law on marine environmental protection is a branch of the law on environmental protection and is the basis for the conduct of marine environmental protection. Since its promulgation in 1982, China’s Marine Environmental Protection Law has undergone two revisions and three amendments, forming a legal system based on the Constitution, with the Environmental Protection Law as the overarching principle, the Marine Environmental Protection Law as the core, and various laws on the protection of marine elements as the gripping force. The revision of the Marine Environmental Protection Law in 2023 was based on the 2018 supervision and inspection of the enforcement inspection team of the Standing Committee of the National People’s Congress, the implementation of the construction of a strong maritime country, and the adaptation to the reform of the ocean governance system. Compared with the previous Marine Environmental Protection Law, the improvements of the newly revised law are mainly reflected in the following: optimizing the institutional mechanism, reflecting the Land and Sea Coordination, strengthening supervision and management, strengthening marine litter pollution prevention and control, enhancing the protection of marine biodiversity, strengthening the regulation of estuaries, and strict liability.